Propuesta de mejora basado en la filosofía lean manufacturing en el proceso productivo de fruta congelada en trozo en una empresa de alimentos (2020)
This monograph proposes the design of an improvement proposal based on the Lean Manufacturing philosophy for the Fruveco company in the frozen fruit production process, which will allow us to understand and identify the most relevant present wastes that imply cost and effort. which consequently does not add value to the process. Initially, the current situation of the production process was diagnosed and the present wastes were determined, through the application of personnel interviews, review of indicators and direct observation of the process.Subsequently, and after the diagnosis, measurement and analysis of the data collected was performed through the use of statistical tools, which finally established a Kaizen-based improvement plan to eliminate the most relevant waste such as waiting times, identified in The dispatch stage also establishes greater precision in production scheduling in order to maintain product inventories that meet the company's needs and ensure timely delivery to the customer.